2020
DOI: 10.21203/rs.3.rs-83179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time Series Analysis of COVID-19 Data to Study the Effect of Lockdown and Unlock in India

Abstract: The ongoing COVID-19 pandemic has caused worldwide socioeconomic unrest, forcing governments to introduce extreme measures to reduce its spread. Being able to accurately forecast the effect of unlocking in India, would allow governments to alter their policies accordingly and plan ahead. The study investigated prediction forecasts using the ARIMA model on the COVID-19 data on the lockdown period and the unlock period. In this work, we have considered not only the no of positive COVID cases but also considered … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another study conducted by Burdick et al 15 in the year 2020, conducted on 197 patients by using supervised learning as their main method. They used classification logistic regression and reported that this algorithm displays higher diagnostic odds ratio (12.58) 18 showed that increase in daily number of tests will result to consecutive increase in daily cases and had reported that a total of 50234 predictive positive cases on 31 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Burdick et al 15 in the year 2020, conducted on 197 patients by using supervised learning as their main method. They used classification logistic regression and reported that this algorithm displays higher diagnostic odds ratio (12.58) 18 showed that increase in daily number of tests will result to consecutive increase in daily cases and had reported that a total of 50234 predictive positive cases on 31 2020.…”
Section: Discussionmentioning
confidence: 99%
“…GIS has recently been used in traffic monitoring, travel industry monitoring, welfare board assessments, and biodiversity protection assessments. PC strategies are progressively being utilised to deduce information from geodatabases [11] .The reason for this study is to give you an overall outline of GIS information designs, information portrayal models, information sources, information mining procedures, SDM apparatuses, difficulties, and obstructions. This review investigates the issues and worries with GIS information and gives a system to tend to them.…”
Section: Introductionmentioning
confidence: 99%